Factors influencing student’s transition from student to workforce in intensive care units - Leonie Olivier; Charlene Downing (Curationis)
Background: Staff shortages, the coronavirus disease 2019 pandemic, increased patient acuity and fiscal restraints contributed to basic nursing students being assigned to intensive care units (ICU). These students, expected to step up and function within the team, were confronted with expectations and situations beyond their clinical preparation for practice. How can we better prepare these students for practice?